Cognitive Competencies Achievement in Application and Analysis Levels for the Topic of Newton Laws at UNTAD Labschool High School - Muslimin, Muslimin; Dwi D.R, Candhra; Nurlaila, Nurlaila (Universitas Muhammadiyah Makassar, 2020)
This study aims to analyze the evaluation in Labschool UNTAD High School Palu. Research data obtained through essay tests and interviews. The cognitive competency test consists of 6 items that were discussed by interviewing 6 selected respondents. Analysis of research data using descriptive-qualitative research. The results showed that this study reached 61.10% or in the very poor category and the level of analysis only reached 25.92% or in the very poor category. Comprehensive analysis application. Better than analysis. From the results obtained can be obtained from students who are able to solve problems, applications that cannot solve problems, category analysis. ointment students, forget, there is no preparation before the exam, less maximum learning in class and no interest in physics.